Performances híbridas no pensamento utópico de Modesto Brocos y Gomez (1852-1936) - Capel, Heloísa Selma Fernandes [UNESP]; Witeze Jr., Geraldo (My University, 2012)
This paper aims to discuss the hybrid performances in the thinking of Modesto Brocos y Gomez. It Uses as source the book Journey to Mars (1930), a fictional work that transits between the utopian genre and the anecdotal mode. For that it discusses the connection of the author to utopian literary genre and its relation to satire, linking them to the discussions of the late nineteenth and early twentieth centuries on the whitening of the Brazilian people, taking also into account his paintings on this subject.
Hybrid performances in the utopian thinking of Modesto Brocos y Gomez (1852-1936)
Keywords: Eugenics; Satire; Utopia